MORAL ANALYSIS IN THE ANIMATED FILMS OF NUSA RARA AND UPIN IPIN AS EDUCATIONAL SHOWS - Wiga Rahmayanti; Ahmad Hariandi; Nopia Wati (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aims to analyze and describe the moral values contained in the Nusa and Rara animations as well as the Upin and Ipin cartoons. This research is a qualitative descriptive research using a sample entitled from the animation film Nussa and Rara and the cartoon Upin Ipin with content analysis techniques. The data in this study contain religious and moral values contained in the animation of Nusa and Rara and Upin and Ipin cartoon. From this research, the results are religious and moral values in form of “adab” before going to bed, eating manners, saying “basmallah”, alms, keeping doing, doing good deeds, tolerance and help, not being arrogant, keeping words, praying on time, brotherhood, honesty, loving animals, respect, responsibility, justice, tolerance, self-discipline, caring for others, courage and democratization. The animation of Nussa Rara as well as the cartoon of Upin and Ipin are highly requested to be watched by children because it contains many religious and moral values in accordance with the national culture and Islam